Senso de coerência materno e alterações dentárias de pacientes com osteogênese imperfeita: um estudo pareado - Suelen Alves Teixeira (2014)
This study aimed to verify the perception of sense of coherence (SOC), among mothers of patients with and without OI, as well as the oral characteristics. A cross-sectional study with 75 parents/guardians and patients with and without OI, aged between 1 and 21 years in a university hospital in Belo Horizonte, in the southeast of Brazil. The oral characteristics of children/adolescents were investigated by clinical examination. The examiners were calibrated to the clinical examination, and obtained kappa values between 0.74 and 1.00. The data were analyzed by means of univariate and bivariate analyzes, considering a reliability level of 95.0%. The present study was approved by the Ethics Committee of the Federal University of Minas Gerais, and will be presented as two manuscripts. The first study analyzed the SOC, among mothers of patients with and without OI. Patients were examined and mothers answered the short version of the instrument SOC Antonovsky (SOC -13), as well as a questionnaire with items related to individual, behavioral and socioeconomic aspects of them and their children. Mothers of patients with OI (72.9%) from a lower social class (85.2%) and those that classified the appearance of their childrens teeth as poor or bad (70.5%) exhibited lower sense of coherence, with statistically significant results (p<0.05). Patients identified with Dentinogenesis Imperfecta (100.00%) and dental caries on one or more teeth (70.5%) were statistically associated with mothers with lower sense of coherence (p<0.005). The SOC was associated with the OI, economic class, mothers perception of the appearance of their childs teeth and the prevalence of Dentinogenesis Imperfecta and dental caries among the patients. The second article aimed to investigate the association between sociodemographic, behavioral and dental characteristics and the presence of OI. In addition to the oral examination of patients, parents/guardians answered a questionnaire on individual, socioeconomic and behavioral aspects of the children. The average age of patients was 8.1 years (±4.4). Among them, 52.0 % were identified with OI (n=39) and 48.0 % without OI (n=36). There was a statistically significant association between the OI and the fact of the patients didnt have received breastfeeding, or have received up to six months (p<0,05). Regarding clinical characteristics, there was a statistically significant relationship between the OI and the presence of Dentinogenesis Imperfecta, developmental defect of enamel, malocclusion and tooth abnormalities (p<0.05). Dental caries and dental trauma were not associated with the presence of OI in children/adolescents (p>0.05). The absence of breastfeeding, or it presence for six months, the presence of Dentinogenesis Imperfecta, developmental defect of enamel, malocclusion and dental anomalies were associated with the presence of OI in children and adolescents.